Application of the Question and Answer Learning Method Through Reasoning Techniques to Improve Learning Activities of Class 6 Students at SDN Sukaharja 1 Telukjambe Timur District, Karawang Regency - Yayat Suryati; Tarpan Suparman (LPPM Universitas Buana Perjungan Karawang, 2021)
The purpose of this study was to determine the increase in student learning activities by using the question and answer method through talaran techniques carried out on grade 6 students of Sukaharja 1 Elementary School, Telukjambe Timur District, Karawang Regency. The research method used is classroom action with observational research techniques, interviews, and tests and documentation. The researcher evaluates the learning process according to the success indicators that have been determined according to the competency standards and basic competencies and compares them with the Minimum Completeness Criteria (KKM), which is 65. The results of the analysis in the first cycle at the fourth meeting show that the value of students is still below the KKM as many as three participants students, with the lowest score of 51, and the class average was 86.16. In the second cycle, it shows an increase in the value of students at the fourth meeting with the lowest score of 70, and none of the students get a score below the KKM. The class average score has increased to 88.25. The learning activities of students had increased, which occurred in the first cycle obtaining an average of 58.10% to 76.51%. Meanwhile, the interviews conducted in the first cycle compared to the second cycle have different activities. In the first cycle, students still acted indifferently when the teacher explained and asked questions. In the second cycle, all students can respond well. The results showed that the application of the learning method through the memorization technique could increase the activity of grade 6 students in participating in learning at the Sukaharja 1 Elementary School, Telukjambe Timur District, Karawang Regency.